(untitled) (Research, Society and Development, 2022)
Introduction: student dropout has always been a problem in the area of information technology, and one of the main causes that influence it is the difficulty that students have in learning programming. In order to alleviate this problem, this article is based on gamification to improve and facilitate the study of programming through the creation of board and digital games. Objective: to create board and digital games to assist in teaching and learning programming for beginning students. Methodology: the project was divided into four phases: search for articles related to the use of games and the facilitation of student learning in programming; soon after, from the answers of a survey, developed previously, the themes used to create the games were chosen, there was the implementation of the board version and the digital version of the games. Results: from the search for materials that were related to the theme, six relevant articles were selected for analysis, according to the pre-determined inclusion and exclusion criteria; from the results of the research that was produced with the aim of detecting the biggest difficulties of the students in the discipline of Algorithms and Logic of programming, the answers were obtained that helped to guide the production of the games. The board versions were produced with draw.io, an online graphics editor, and the digital versions were developed with the Flippity tool, used to create different types of games.